Identification of fruit yield loci controlling the salt tolerance conferred by solanum rootstocks - Estan, M. T.; Villalta, Irene; Bolarin, M. C.; Carbonell, Emilio A.; Asins, María J. (2017)
The rootstock effect on the fruit yield of a grafted tomato variety was genetically analyzed under salinity using as rootstock two populations of F(9) lines developed from a salt sensitive genotype of Solanum lycopersicum var. cerasiforme, as female parent, and two salt tolerant lines, as male parents, from S. pimpinellifolium, the P population ( 123 lines), and S. cheesmaniae, the C population ( 100 lines). There were rootstock lines from the two populations ( up to 65% in the P population) that raised the fruit yield of the commercial hybrid under saline conditions. It is shown that this salt tolerance rootstock effect is a heritable trait ( h(2) near 0.3), governed by at least eight QTLs. The most relevant component was the number of fruits. Thus most detected QTLs correspond to this component. In general, QTL gene effects are medium-sized, with contributions from 8.5 up to 15.9% at most, and the advantageous allele comes from the wild, salt tolerant species. Only two fruit yield QTLs on chromosomes P9 and C11 might correspond to fruit yield QTLs of the non-grafted lines indicating their root system dependence. A fruit yield QTL on chromosome 3 is acting epistatically in both populations. The epistatic interactions found were dominant and they were unveiled using the associated marker as cofactor in the composite interval mapping methodology. Therefore, an efficient and profitable utilization of wild germplasm can be carried out through the improvement of rootstocks that confer salt tolerance in terms of fruit yield to the grafted variety.